2017
DOI: 10.3389/fpsyg.2017.01726
|View full text |Cite
|
Sign up to set email alerts
|

Deep Convolutional Neural Networks Outperform Feature-Based But Not Categorical Models in Explaining Object Similarity Judgments

Abstract: Recent advances in Deep convolutional Neural Networks (DNNs) have enabled unprecedentedly accurate computational models of brain representations, and present an exciting opportunity to model diverse cognitive functions. State-of-the-art DNNs achieve human-level performance on object categorisation, but it is unclear how well they capture human behavior on complex cognitive tasks. Recent reports suggest that DNNs can explain significant variance in one such task, judging object similarity. Here, we extend these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
152
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(163 citation statements)
references
References 27 publications
10
152
1
Order By: Relevance
“…More recently, it was shown that human shape sensitivity for natural images could be explained well for the first time using deep neural networks (Kubilius, Bracci, & Op de Beeck, 2016), which now constitute a near essential baseline for emerging models of human shape perception (Erdogan & Jacobs, 2017). A follow-up to our own previous work (Peterson, Abbott, & Griffiths, 2016) showed that important categorical information is missing from deep representations (Jozwik, Kriegeskorte, Storrs, & Mur, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…More recently, it was shown that human shape sensitivity for natural images could be explained well for the first time using deep neural networks (Kubilius, Bracci, & Op de Beeck, 2016), which now constitute a near essential baseline for emerging models of human shape perception (Erdogan & Jacobs, 2017). A follow-up to our own previous work (Peterson, Abbott, & Griffiths, 2016) showed that important categorical information is missing from deep representations (Jozwik, Kriegeskorte, Storrs, & Mur, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…Interactions among these three research domains have not been as intimate as one would hope. The domains of object vision and semantic cognition have been getting closer, both by the fact that semantic cognition researchers often examine the nature of natural object representations at both visual and semantic levels Martin et al 2018), and also that both domains are relying increasingly on the use of advanced neural network models to reveal statistical regularities in object representation (Jozwik et al 2017;Devereux et al 2018). However, the episodic memory domain has been somehow disconnected from the other two, partly because it has tended to focus on broad categorical distinctions (e.g., faces vs. scenes) rather than in the component visual or semantic features (Lee et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, modern computational approaches to object recognition emphasize image statistics 39 or hierarchical feature extraction operations such as those implemented by convolutional neural networks (CNNs) 40,41 . Yet, without explicitly invoking any skeletal description, these models match human performance on object recognition tasks 41 , and they are predictive of both human behavioral and neural responses [42][43][44] . Even models that do emphasize global shape properties do so by describing the local properties of components parts (e.g., geons) and coarse, categorically-defined, spatial relations 12,45 , not a skeletal structure.…”
mentioning
confidence: 99%